Islam Zaman Modern Dan Kontemporer Melalui Organisasi Politik Dan Sosial di Indonesia - Basri, Muhammad; Marito, Sulaika; Fitri Khairiyah , Annisa Fitri Khairiyah (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
This research explores the roles, challenges, and opportunities faced by Islamic political and social organizations in navigating the complex dynamics of contemporary society. With a focus on the contributions of Islamic political and social organizations in shaping Islamic values in various global contexts, this study employs a qualitative literature review method to investigate the historical development of Islamic political organizations and the contributions of Islamic social organizations in community empowerment and addressing social issues. Source and reference identification involve searching books, journals, articles, and relevant electronic sources, with strict inclusion and exclusion criteria to ensure the quality and relevance of the information. The research findings provide in-depth insights into how Islamic political organizations contribute to shaping policies and governance in line with Islamic principles, while Islamic social organizations focus on community empowerment and addressing social issues. Challenges in implementing Islamic values include differences in the interpretation of religious teachings, resistance from specific groups, and the complexity of social and political dynamics. Meanwhile, opportunities for development include leveraging technology, fostering collaboration between organizations, and improving access to education and healthcare.